A Staged Approach to Combined Extra-articular Limb Deformity Correction and Total Ankle Arthroplasty for End-Stage Ankle Arthritis. (March 2021) - Day, Jonathan; Principe, Peter S.; Caolo, Kristin C.; Fragomen, Austin T.; Rozbruch, S. Robert; Ellis, Scott J.
Background: Patients presenting with end-stage ankle osteoarthritis (OA) in the setting of a concomitant extra-articular limb deformity pose a challenging problem that has not yet been described in the literature. We describe a case series of patients treated with external and internal fixation techniques followed by total ankle arthroplasty (TAA) in a staged approach to treat this complex presentation. Methods: Eight patients with limb deformity and end-stage ankle OA who underwent staged deformity correction and TAA from 2016 to 2019 at our institution were retrospectively identified. Average age was 58.5 (range, 49-68) years, with an average follow-up of 2.6 (range, 0.8-4.2) years. All patients underwent limb reconstruction with either tibial osteotomy with a circular frame (n=6) or intramedullary nail (n=2). Limb deformities consisted of the following: posttraumatic tibial malunion (2), limb length discrepancy (1), acquired tibial deformity (1), genu varum (2), or genu valgum (2). Radiographic parameters were assessed pre- and postoperatively on 51-inch standing and ankle radiographs: limb length discrepancy (LLD), genu varum/valgum deformity, recurvatum deformity, mechanical axis deviation, medial proximal tibial angle, lateral distal tibial angle, anterior distal tibial angle, and tibiotalar alignment. Pre- and postoperative patient-reported outcomes were assessed using 2 metrics, the Limb Deformity–Scoliosis Research Society (LD-SRS) and Patient-Reported Outcomes Measurement Information System (PROMIS) scores (Physical Function, Pain Intensity, Pain Interference, Global Physical Function, and Global Mental Function). Results: Following staged limb deformity correction and TAA, all patients achieved correction of LLD and angular deformities of the lower limb, along with restoration of normal alignment of the ankle joint. There was significant mean improvement in all patient-reported LD-SRS and PROMIS domains, except for LD-SRS mental health. LD-SRS function improved from 2.6 (±0.7) to 4.6 (±0.2), P = .008; pain improved from 2.9 (±0.9) to 4.8 (±0.2), P = .012; self-image improved from 2.9 (±0.4) to 4.7 (±0.3), P < .001; and total LD-SRS improved from 3.3 (±0.4) to 4.8 (±0.2), P = .002. Average satisfaction was 4.9 (±0.3). PROMIS physical function improved from 32.3 (±6.8) to 51.3 (±5.3), P = .008; pain interference improved from 66.0 (±9.1) to 41.3 (±6.2), P = .004; pain intensity improved from 60.0 (±13.3) to 33.1 (±5.3), P = .007; global physical health improved from 39.3 (±6.8) to 60.7 (±5.1), P = .002; global mental health improved from 54.8 (±5.9) to 65.6 (±2.8), P = .007. There was one incidence of pin site infection and one reoperation. Conclusion: Deformity correction with either external frame or intramedullary nail fixation followed by TAA in a staged approach was a viable surgical option in the treatment of end-stage ankle OA with concurrent extra-articular limb deformity. This unique approach was capable of achieving deformity correction with improved patient-reported outcomes, minimal complications, and good patient satisfaction. Level of Evidence: Level IV, retrospective case series.